DUPLA MODIFICAÇÃO QUÍMICA DE AMIDO DE FEIJÃO, AVALIAÇÃO DAS PROPRIEDADES TECNOLÓGICAS E APLICAÇÃO EM MATRIZ PROTEICA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2017)
Common beans are highly consumed in Brazil, mainly in complement with rice. It is a nutritious food source, riches in carbohydrates that represent 60% of the dry weight of the grains which starch is the largest fraction. Starch is a natural polymer of glucose and it is considered as an energy reserve of the higher vegetables. Found as semicrystalline granules, starch is a mixture of amylose and amylopectin molecules and this one has a greater content. In its native form, starch presents limited application, especially as a binding agent, due their low thermal resistance and high tendency to retrograde. Therefore, physical and/or chemical modifications can be applied in order to improve technological properties, making starch viable at industrial level. The present study aimed to extract bean starch, analyze their physical-chemical and technological properties, modify by oxidation, acetylation and dual-modification, as well as their application in breaded products. The X-ray diffractograms showed that bean starch has a type C, typical of legumes. Images of electron microscopy revealed that the granules has an oval and elliptical shape. The oxidation of the starch was evidenced by the increase of carbonyl and carboxyl contents. Acetylated samples presented a low degree of substitution, that allow food application. Substitution of hydroxyls was proved by acetyl groups that exhibits bands in the region of 1735-1740 cm-1. Modified starches showed changes in their technological properties. Oxidized sample presented increase of the peak and setback viscosity, due carboxylic groups. The acetylated starch presented cooking stability, due their low breakdown viscosity. Enthalpies of gelatinization of the modified samples reduced, in function of weakening of the granular structure. Relative crystallinity, hardness and adhesiveness of the gels, also reduced. Application of bean starch in breaded products exhibited interesting results. The system with oxidized starch resulted in the most crust covered area after frying, 72%. Breaded meat presented yield up to 100%, that means weight gain during the process. The pick-ups values of samples with starch were less than 30%, then the fried products can be classified as breaded. Batter containing oxidized starch resulted in the lowest absorption oil and the highest hardness, which may be associated with the amylose content. The use of modified bean, an unconventional botanical source of starch, proved to be possible due their technological properties and the results of breaded products.
Keywords: Phaseolus vulgaris L.; oxidação; acetilação; dupla-modificação; empanado; batter; breader; textura; Phaseolus vulgaris L.; oxidation; acetylation; dual-modification; breaded; batter; breader; texture; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS